(3cJGH aj GdSehe Ydi ePgH GdcdOGfjjfs - (3CMeO Hf Ydj Hf bjS Hf GdeNJGQ Hf YHO GdcQje Hf MQjKG, GHf hMTjI,J (B291 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI gPG cJGH GedGg GHh HcQ CMeO Hf Ydi bGd LeYJ eG ajg ef GdcdGe Ydi GdSehe hYdGLGJgG ef cJGH hLOJg ef cJH QLd ef bOeGA GdcSOGfjjf s
(3BNQgG (B:s
(3hefj LYd gPG GdOhGA Ydi ehVY UMjM ef GdHOf GQNLI hGHcGg hChLYg s
(3HgG fXGe GdJYbjHIs
(3fbdI cJGH HQHhbGaj GdSehe ef G dfHWjI Edj GdYQHjI GHf hMTjI GdeUfa hjJdhg ChQGb HgG ahGFO WHjIs
(3eUOQ GbJfGA GdCUd (B:s
(3HJRjG (B- (3ghdfOG s
Keywords: (3GdcjejGA h GdWHjYjGJs